2018
DOI: 10.1158/0008-5472.can-17-3614
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2 Mediates Neutrophil Killing of Disseminated Tumor Cells

Abstract: Neutrophils play a critical role in cancer, with both protumor and antitumor neutrophil subpopulations reported. The antitumor neutrophil subpopulation has the capacity to kill tumor cells and limit metastatic spread, yet not all tumor cells are equally susceptible to neutrophil cytotoxicity. Because cells that evade neutrophils have greater chances of forming metastases, we explored the mechanism neutrophils use to kill tumor cells. Neutrophil cytotoxicity was previously shown to be mediated by secretion of H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 44 publications
1
131
0
1
Order By: Relevance
“…Recent studies have identified a population of circulating LDNs in tumor-bearing mice that resemble either mature or immature cells in terms of heterogeneous composition, similarly to the LDNs described in the blood of cancer patients [122]. However, unlike humans, the two subtypes of circulating mature neutrophils from tumor-bearing mice, which separated within the NDN and LDN layers following density gradient centrifugation, were reported to display opposing functional properties [122,123]. Specifically, NDNs displayed direct tumor cytotoxicity and antitumor properties [123], whereas LDNs were immunosuppressive and more tumor-permissive than the other population ex vivo and in vivo [122] (Figure 4).…”
Section: Micementioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have identified a population of circulating LDNs in tumor-bearing mice that resemble either mature or immature cells in terms of heterogeneous composition, similarly to the LDNs described in the blood of cancer patients [122]. However, unlike humans, the two subtypes of circulating mature neutrophils from tumor-bearing mice, which separated within the NDN and LDN layers following density gradient centrifugation, were reported to display opposing functional properties [122,123]. Specifically, NDNs displayed direct tumor cytotoxicity and antitumor properties [123], whereas LDNs were immunosuppressive and more tumor-permissive than the other population ex vivo and in vivo [122] (Figure 4).…”
Section: Micementioning
confidence: 97%
“…However, unlike humans, the two subtypes of circulating mature neutrophils from tumor-bearing mice, which separated within the NDN and LDN layers following density gradient centrifugation, were reported to display opposing functional properties [122,123]. Specifically, NDNs displayed direct tumor cytotoxicity and antitumor properties [123], whereas LDNs were immunosuppressive and more tumor-permissive than the other population ex vivo and in vivo [122] (Figure 4). However, the mechanisms leading to functional differences between mature NDNs and LDNs remain unknown.…”
Section: Micementioning
confidence: 99%
“…Saito et al [177] reported that neutrophils activate an oxidative process at the contact site with tumor cells and have the capacity to limit metastatic spread. Recently, Gershkovitz et al [178] described in a 4T1 breast tumor model that neutrophil cytotoxicity toward tumor cells is mediated via the activation of TRPM2, an H 2 O 2 -dependent Ca 2+ channel, in tumor cells. The authors showed that TRPM2-deficiency reduces mammary tumor cells (human and mouse) susceptibility to neutrophil cytotoxicity.…”
Section: Antitumor Effects Of Tansmentioning
confidence: 99%
“…[3][4][5] Several studies have provided compelling evidence for neutrophils' protumorigenic role, 6,7 while others have advocated for neutrophils antitumor and antimetastatic potential. 8,9 It is now generally accepted that neutrophils can acquire both pro-or antitumor function as part of an immunosuppressive switch occurring in cancer. 10,11 Neutrophilia has been extensively described in cancer patients, but no clear correlation between absolute neutrophil count (ANC) and prognosis has been so far validated.…”
Section: Introductionmentioning
confidence: 99%